Lung function after allogeneic bone marrow transplantation for leukaemia or lymphoma. Issue 5 (May 1996) - Nysom, K; Holm, K; Hesse, B; Ulrik, C S; Jacobsen, N; Bisgaard, H; Hertz, H
Abstract : Longitudinal data were analysed on the lung function of 25 of 29 survivors of childhood leukaemia or lymphoma, who had been conditioned with cyclophosphamide and total body irradiation before allogeneic bone marrow transplantation, to test whether children are particularly vulnerable to pulmonary damage after transplantation. None developed chronic graft-versus-host disease. Transfer factor and lung volumes were reduced immediately after bone marrow transplantation, but increased during the following years. However, at the last follow up, 4-13 years (median 8) after transplantation, patients had significantly reduced transfer factor, total lung capacity, and forced vital capacity (-1.0, -1.2, and -0.8 SD score, respectively), and increased ratio of forced expiratory volume in one second to forced vital capacity (+0.9 SD score). None of the patients had pulmonary symptoms, and changes were unrelated to their age at bone marrow transplantation. In conclusion, patients had subclinical restrictive pulmonary disease at a median of eight years after total body irradiation and allogeneic bone marrow transplantation.